Kandungan Beberapa Zat Endogen pada Buah Retensi dan Buah akan Rontok pada Mangga - Sakhidin Sakhidin; Bambang S. Purwoko; Sudirman Yahya; R. Poerwanto; Slamet Susanto; A. S. Abidin (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2006)
The aim of this research was to study the relationship between fruit drop  and contents of auxin, polyamines, ACC, total sugar, and starch. Cultivars of mango used were Gadung 21 and Lalijiwo.The persisting fruit and abscising fruits were used to quantify auxin, polyamine, ACC, total sugar, and starch.  The content of polyamine and ACC was determined on pericarp, auxin on seed, whereas the content of starch and total sugar was determined on mesocarp. The result of research showed that fruit drop was preceded by low content of auxin that increased the sensitivity of abscission zone to ethylene.  The increased sensitivity of abscission zone to ethylene was supported by low content of polyamine and  high content of ACC. The abscising fruit has high content of starch, but low in  total sugar content.   Key words : Mango, persisting fruit, abscising fruit, auxin, polyamine, ACC, total sugar, starch